Associations Between Sleep and Mental Health Among Latina Adolescent Mothers: The Role of Social Support - Yung, Shun Ting; Main, Alexandra; Walle, Eric A.; Scott, Rose M.; Chen, Yaoyu (Frontiers in Psychology, 2021)
Adolescent mothers experience poorer sleep than adult mothers, and Latina adolescent mothers are at greater risk of postpartum depression compared with other racial/ethnic groups. However, social support may be protective against the negative effects of poor sleep in this population. The current study examined (1) associations between the quality and quantity of Latina adolescent mothers’ sleep and mental health (depressive symptoms and anxiety), and (2) whether social support buffered the effects of poor sleep on mental health. A sample of Latina adolescent mothers (N = 84) from an agricultural region in the United States reported on their sleep duration/quality, social support from family, friends, and significant others, and their depressive and anxiety symptoms. Results showed that adolescent mothers reported poorer sleep than pediatric recommendations, and poorer sleep quality was associated with greater depressive and anxiety symptoms. Interestingly, when adolescent mothers reported better sleep, they had fewer depressive symptoms in the context of high support from friends compared with low support from friends. Sleep is important for mental health in Latina adolescent mothers, and better sleep combined with strong social support has positive associations with mental health in this population. Findings hold implications for improving mental health in adolescent mothers.